2-[18F]FDG PET in the Management of Radioiodine Refractory Differentiated Thyroid Cancer in the Era of Thyrosin-Kinases Inhibitors: A Real-Life Retrospective Study - Stefano Gay; Stefano Raffa; Anna De’Luca di Pietralata; Matteo Bauckneht; Lara Vera; Alberto Miceli; Manuela Albertelli; Silvia Morbelli; Massimo Giusti; Diego Ferone (Diagnostics, 2022)
Purpose To evaluate the role of 2-[18F]FDGPET/CT in the follow-up of radioiodine refractory thyroid cancer (RR-TC). Methods Forty-six 2-[18F]FDGPET/CT scans from 14 RR-TC patients were considered. Thyroid function tests: thyroglobulin (Tg), levothyroxine (LT4), and tyrosine-kinases inhibitors (TKIs) assumptions were recorded. Metabolic tumour volume (MTV) and total lesion glycolysis (TLG) were calculated from each scan and correlated with clinical parameters and the overall survival (OS). Results Baseline TLG and MTV predicted OS (p = 0.027 and p = 0.035), and negative correlation with OS was also confirmed when the same parameters were measured in follow-up scans (p = 0.015 and p = 0.021). Tg also correlated with the OS; (p = 0.014; p = 0.019 and p = 0.009). However, TLG and MTV were not significantly correlated with Tg levels. MTV and TLG variation in time were reduced during TKI therapy (p = 0.045 and p = 0.013). Conclusions 2-[18F]FDGPET/CT confirmed its prognostic role at the first assessment and during the follow-up of RR-TC patients. 2-[18F]FDGPET/CT parameters seem at least partially independent from Tg. TKI therapy resulted in a measurable effect on the variation of 2-[18F]FDGPET/CT parameters over time.